CUTA4UML: bridging the gap between informal and formal requirements for dynamic system aspects - Erfurth, Ivonne; Rossak, Wilhelm (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
In this paper, we describe our integrated approach to improve requirements elicitation and system specification by supporting a strong and direct involvement of all stakeholders, including non technical personnel, in the early phases of a project. This so-called CUTA4UML approach comprises a framework of methods, tools and feedback cycles that is based on the concept of Participatory Design (PD) and instantiated via an extended version of a user-driven "card game" (CUTA). This card game can be executed on paper or via electronic means. Our focus will be on the system's dynamic aspects which are, always, especially tricky to cover. We will also take a closer look at the inherently involved problem to match the rather informal results of such an card-based approach to a quite formal (UML -- Activity Diagrams) modeling technique -- a step necessary to make the results useful in a structured development process and, so far, one of the weak points in all of these approaches. All our concepts and conclusions are based on a sound experimental basis and have been evaluated and discussed with industrial partners, mostly in a context of small and medium sized companies.